Model of Vocational Madrasah Based Student Entrepreneurship Skill Development Through Religious Values - Tuti Kamila Sukma; Nur Wahid, Reza; Putri, Jessica Aulia; Evanita, Susi; Friyatmi (AI Society & STMIK Indonesia, 2023)
The mission of MAN 1 Kota Bukittinggi, a vocational school that instills strong religious values in its students, is to develop students with entrepreneurial insights and vocational skills needed for future survival, as well as an entrepreneurial spirit in accordance with Islamic law. This research seeks to investigate the techniques and methods used by MAN 1 Kota Bukittinggi, a vocational madrasah, in developing the entrepreneurial character of its students while preserving Islamic teachings. This study uses a descriptive-qualitative methodology, by combining interview techniques and field observations. The results of the study show that by educating students starting from religious observance, personality development, application of self-discipline, creativity, and self-confidence and strong responsibility as an entrepreneur, as well as by providing insight and skills that must be mastered, students can be directed to enjoy the world of entrepreneurship.